In situ detection of transcripts for ribulose-1,5-bisphosphate carboxylase in cyanobacterial heterocysts. - Madan, A P (1993)
Heterocysts of free-living cyanobacteria lack ribulose-1,5-bisphosphate carboxylase activity. Nevertheless, using in situ hybridizations, we demonstrate that transcripts for the rbcL and rbcS genes are present in both heterocysts and vegetative cells of Anabaena spp. in association with, or isolated from, the Azolla-Anabaena symbiosis. In contrast, rbcLS transcripts were detected only in vegetative cells of the free-living cyanobacterium Anabaena strain 7120. Under anaerobic growth conditions that inhibited heterocyst differentiation, transcripts for nitrogenase were present in all cells composing Anabaena strain 7120 filaments, whereas rbcL and rbcS transcripts were not detected. Thus, transcriptional regulation of genes related to photosynthesis and nitrogen fixation is under environmental, as well as developmental, control in Anabaena spp. In addition, these results suggest either the possible retention of regulatory patterns in symbiotically derived cyanobacterial isolates or differences in expression of rbcLS genes in different free-living cyanobacteria.